(untitled) (Praxis Educativa, 2012)
The article offers a brief summary of the history of the concept of family together with the changes that the family system has undergone along times, and especially during the past fifty years. It describes different family patterns of our times, and also establishes a relation between social and family crises, to later introduce reflections about family / families’ future. The article approaches, then, the issue of gender by calling it “the invisible fabric”, providing a conceptualization of feminism and analyzing patriarchal premises and assumptions. On the basis of reflections generated by those assumptions, it opens new possibilities to de-construct and re-construct gender concepts. By the end of the discussion, the connection between gender and school is presented, offering a space for questions and proposals.